ANSWER
See below
EXPLANATION
Given
![f(x) = \frac{ {x}- 9 }{x + 5}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%5Cfrac%7B%20%7Bx%7D-%209%20%7D%7Bx%20%2B%205%7D%20)
and
![g(x) = \frac{ - 5x - 9}{x - 1}](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%20%20%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%20)
![(f \circ \: g)(x)= \frac{ (\frac{ - 5x - 9}{x - 1})- 9 }{(\frac{ - 5x - 9}{x - 1} )+ 5}](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%28%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%29-%209%20%7D%7B%28%5Cfrac%7B%20-%205x%20-%209%7D%7Bx%20-%201%7D%20%29%2B%205%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9 - 9(x - 1)}{x - 1}}{\frac{ - 5x - 9 + 5(x - 1)}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209%20-%209%28x%20-%201%29%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20-%209%20%2B%205%28x%20-%201%29%7D%7Bx%20-%201%7D%20%7D%20)
Expand:
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9 - 9x + 9}{x - 1}}{\frac{ - 5x - 9 + 5x - 5}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209%20-%209x%20%20%2B%209%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20-%209%20%2B%205x%20-%205%7D%7Bx%20-%201%7D%20%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 5x - 9x + 9 - 9}{x - 1}}{\frac{ - 5x + 5x - 5 - 9}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%205x%20-%209x%20%20%2B%209%20-%209%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-%205x%20%2B%205x%20-%205%20-%209%7D%7Bx%20-%201%7D%20%7D%20)
![(f \circ \: g)(x)= \frac{ \frac{ - 14x }{x - 1}}{\frac{ -14}{x - 1} }](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%20%5Cfrac%7B%20%5Cfrac%7B%20-%2014x%20%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B%20-14%7D%7Bx%20-%201%7D%20%7D%20)
Since the denominators are the same, they will cancel out,
![(f \circ \: g)(x)= \frac{ - 14x}{ - 14} = x](https://tex.z-dn.net/?f=%28f%20%5Ccirc%20%5C%3A%20g%29%28x%29%3D%20%5Cfrac%7B%20-%2014x%7D%7B%20-%2014%7D%20%20%3D%20x)
Answer:
60
Step-by-step explanation:
because 12 inches is one foot so there’s 6 feet per 6 feet of ribbon and there’s 10 of these ribbons so 6 times 10 is 60
You would do 2x-3+x+3x-15=360
combine like terms which then gives you
5x-18=360 then you would add 18 to both sides giving you
5x=378
and then you divide by 5 on both sides which will then give you your answer x=?
Answer:
Step-by-step explanation:
We know that when there is an absolute value sign, the value inside the bars is always positive.
- => I3x + 3I = 10
- => 3x + 3 = 10
- => 3x = 10 - 3
- => 3x = 7
- => x = 7/3
- => x = 2.33 (Rounded to nearest hundredth)
Hence, the value of x is 2.33.